Facies distribution, its implications for climate signals, and hydrocarbon potential of the Permian Lyons Sandstone, Front Range Basin, northern Colorado, USA - Kendigelen, Oguzhan, author; Egenhoff, Sven, advisor; Stright, Lisa, committee member; Omur-Ozbek, Pinar, committee member (Colorado State University. Libraries, 2016)
The Permian Lyons Formation consists of mostly fine- to medium-grained sandstones with minor silt- and mudstone intercalations. The formation shows six siliciclastic facies that are grouped into two Facies Associations: Facies Association 1 consists of high-angle cross-laminated sandstones (Facies 1), low-inclined cross-laminated sandstones (Facies 2), horizontally-laminated sandstones (Facies 3), and chaotically-bedded to folded sandstones (Facies 4), while Facies Association 2 is mainly characterized by wavy- to irregularly-laminated silty sandstones (Facies 5) and massive to wavy-laminated silt-rich mudstones (Facies 6) with minor amounts of high-angle cross-laminated sandstones (Facies 1), low-inclined cross-laminated sandstones (Facies 2) and horizontally-laminated sandstones (Facies 3). Facies Association 1 deposits dominate the southern part of the study area whereas Facies Association 2 sediments are more common towards to north. Stratigraphically, Facies Association 1 and 2 deposits occur intercalated with each other, and generally show two time Facies Association 2 sediments overlain by Facies Association 1 deposits. This intercalation of Facies Associations is best observed in the central part of the study area. In the south, Facies Association 1 deposits strongly dominate the succession, and in the north Facies Association 2 deposits are much more common, and do not show intercalation clearly. In the Lyons Formation, high-angle cross-laminated sandstones (Facies 1) are interpreted as remnants of fossil eolian dunes. Between these dunes, nearly flat to low-inclined dry interdunal areas occur and they are characterized by low-inclined cross-laminated sandstones (Facies 2) and horizontally-laminated sandstones (Facies 3). Chaotically-bedded to folded sandstones (Facies 4) represent internal deformation of dune deposits in the lower portion of dune flanks. Deposition of wavy- to irregularly-laminated sandstones (Facies 5) reflects wet to damp conditions in interdune areas. Massive to wavy-laminated silt-rich mudstones (Facies 6) indicate the presence of small ponds or lakes between dunes. Facies Association 1 deposits overall represent dry eolian conditions, and Facies Association 2 deposits represent wet eolian conditions. The distribution of Facies Association therefore indicates that dry and wet climates were generally alternating but overall dry climate conditions dominated the southern part of the study area whereas wet conditions were more prevalent in the north. Stratigraphically, the north to south transect reflects an expansion of dry conditions northwards despite the climate fluctuations, and a “Goldilocks” window of where to best observe climate cycles in the central part of the study area. This change in depositional conditions is exclusively observed along a north-south transect but not evident in an east-west direction. This study interprets the parts of the succession where Facies Association 1 sediments dominate as the paleo-erg center, and the portions where wet Facies Association 2 deposits are more prevalent as a paleo-erg margin environment. In the Lyons Formation, dry eolian deposits show good reservoir quality because of overall excellent sorting and roundness of the grains, while wet eolian deposits contains more fine-grained sediment which causes poorly sorting and reduction of porosity. Therefore, this study interprets that the main Lyons Formation plays are in the southern part of the study area within the paleo-erg center where dry eolian deposits are strongly dominating.